Research on the top cutting features on face gears using normal to tooth profile method - Wei Sheng; Zhengminqing Li; Xiaofeng Yu (Engineering Science and Technology, an International Journal, 2024)
In the field of face gear tooth profile research, while the phenomena of undercutting and pointing are widely recognized, the occurrence of tooth top overcut is often overlooked. This paper employs the Normal to Tooth Profile Method (NTPM) to construct a mathematical model for the face gear tooth surface, encompassing the working surface, fillet surface, and top cutting surface. The tooth top overcut phenomenon is elucidated by means of tooth surface visualization and simulated gear cutting. The reliability of the proposed model is also compared with traditional models through the use of finite element simulations and tooth contact experiments. The study also analyzes the influence of design parameters on the amount of overcut and provides chamfering recommendations to eliminate it. The findings reveal that tooth top cutting is particularly significant in face gear pairs with high gear ratios, necessitating special attention when designing power-split transmission systems. Furthermore, the proposed NTPM is a more effective method for examining face gear tooth profile characteristics.